Incidence of postoperative pain after single-visit and multiple-visit root canal therapy: a systematic review - Gunjan Kumar; Samikshya Jena; Nisha Manila; Mohammad Fareed; Mohmed Isaqail Karobari (BMC Oral Health)
Abstract AIM- The objective of the systematic review is to evaluate the incidence of postoperative pain after single-visit and multiple-visit root canal therapy. METHODS- Published research indexed in PubMed or Scopus or Cochrane or DOAJ or Web of Science evaluating the frequency percentage of postoperative aching after one and several root canal therapy appointments through randomized controlled trials or prospectively were included. RESULT- Most surveys utilized VAS (Visual Analogue Scale) to estimate the degree of pain among the participants. The majority of the studies (n-8) showed no difference between postoperative pain during single-sitting endodontic treatment or multiple-sitting endodontic treatment. On the contrary, several studies (n-6) also revealed that post-obturation pain in a single-appointment root canal therapy is less compared to multi-visit root canal therapy. The current research results give insight into the incidence of postoperative endodontic pain among the study participants undergoing root canal treatment through single or multiple visit appointments. CONCLUSION- The lack of consistency between studies is due to the different ways in which pain intensity is measured and differences in treatment methods, patient selection and treatment outcomes.